Central nervous system tumors in adolescents and young adults: a society for neuro-oncology consensus review on diagnosis, management, and future directions - Lim-Fat, Mary Jane; Bennett, Julie; Ostrom, Quinn; Touat, Mehdi; Franceschi, Enrico; Schulte, Jessica; Bindra, Ranjit S; Fangusaro, Jason; Dhall, Girish; Nicholson, James; Jackson, Sadhana; Davidson, Tom Belle; et al. (Neuro-Oncology, 2025)
Adolescents and young adults (AYAs; ages 15-39 years) are a vulnerable population facing challenges in oncological care, including access to specialized care, transition of care, unique tumor biology, and poor representation in clinical trials. Brain tumors are the second most common tumor type in AYA, with malignant brain tumors being the most common cause of cancer-related death. The 2021 WHO Classification for central nervous system (CNS) Tumors highlights the importance of integrated molecular characterization with histologic diagnosis in several tumors relevant to the AYA population. In this position paper from the Society for Neuro-Oncology (SNO), the diagnosis and management of CNS tumors in AYA is reviewed, focusing on the most common tumor types in this population, namely glioma, medulloblastoma, ependymoma, and CNS germ cell tumor. Current challenges and future directions specific to AYA are also highlighted. Finally, possible solutions to address barriers in the care of AYA patients are discussed, emphasizing the need for multidisciplinary and collaborative approaches that span the pediatric and adult paradigms of care, and incorporating advanced molecular testing, targeted therapy, and AYA-centered care.